2002
DOI: 10.1097/00000542-200208000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Tranexamic Acid during Cardiopulmonary Bypass

Abstract: Tranexamic acid pharmacokinetics are influenced by CPB. Our TA pharmacokinetic model does not provide support for the wide range of TA dosing techniques that have been reported. Variation in TA efficacy from study to study and confusion about the optimal duration of TA treatment may be the result of dosing techniques that do not maintain stable, therapeutic TA concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
183
5
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(205 citation statements)
references
References 28 publications
14
183
5
3
Order By: Relevance
“…Various studies have been performed with the aim of identifying the correct dosage of TnX-A. A bolus dose of 10 mg/kg in 20 min before cutaneous incision followed by infusion at the rate of 1 mg/kg per hour has been suggested as the ideal dosage for bleeding control, and increasing the dosage has been reported as having no additional beneficial effects on bleeding control (19)(20)(21). Similar to our study, the highest level of postoperative bleeding was observed in the postoperative first 3 h. We similarly initiated TnX-A infusion with skin incision at the dosage as described.…”
Section: Tnx-a (N = 18)mentioning
confidence: 99%
“…Various studies have been performed with the aim of identifying the correct dosage of TnX-A. A bolus dose of 10 mg/kg in 20 min before cutaneous incision followed by infusion at the rate of 1 mg/kg per hour has been suggested as the ideal dosage for bleeding control, and increasing the dosage has been reported as having no additional beneficial effects on bleeding control (19)(20)(21). Similar to our study, the highest level of postoperative bleeding was observed in the postoperative first 3 h. We similarly initiated TnX-A infusion with skin incision at the dosage as described.…”
Section: Tnx-a (N = 18)mentioning
confidence: 99%
“…5,7 An initial TXA bolus of 30 mgÁkg -1 was infused over 15 min followed by a 16 mgÁkg -1 Áhr -1 infusion until chest closure with a 2 mgÁ kg -1 load in the pump prime. Blood samples were obtained at baseline, five minutes after the bolus, five minutes before and after commencing CPB, and at 30-min intervals whilst on CPB.…”
Section: Methodsmentioning
confidence: 99%
“…6 Optimal dosing of TXA is still unknown and several theoretical models have been developed and applied. One of the most popular dosing regimens is based on the pharmacokinetic model developed by Dowd et al 7 It has been used in a randomized controlled trial comparing the use of three antifibrinolytic agents in high-risk cardiac surgical patients [Blood Conservation Using Antifibrinolytics in a Randomized Trial (BART)]. 5 The plasma concentrations of TXA in patients undergoing cardiac surgery with these antifibrinolytic doses have not been studied.…”
Section: Résumémentioning
confidence: 99%
“…Em trabalho recente, publicado por Fiechtner e col. 65 , a dose descrita manteve níveis séricos adequados (↑ 10 µg.mL -1 ). Esse regime de administração foi questionado por estudo preliminar, realizado por Dowd e col. 66 …”
Section: áCido Tranexâmicounclassified
“…In a recent study by Fischer et al 65 , the dose described maintained adequate levels (↑ 10 µg.mL -1 ). This administration regimen was questioned by a preliminary study by Dowd et al 66 , who measured serum levels of TA during CPB. The administration of 10 mg.kg -1 of TA followed by the infusion of 1 mg.kg -1 .h -1 did not maintain therapeutic levels in isolated moments of CPB.…”
Section: Tranexamic Acidmentioning
confidence: 99%